Smart Cities and Aging Well: Exploring the Links between Technological Models and Social Models for Promoting Daily Social Interaction for Geriatric Care - Kiss, Jocelyne; A Reyes, Miguel; Hutson, James (Journal of Community Medicine and Health Solutions, 2024)
The aging global population requires a new social model to meet the growing social, economic, and physical needs of seniors. Western social models need to be reconsidered in light of examples that support communal ways of living, which are sustainable through smart city design for more supportive geriatric care systems. To address the complex problems of geriatric care in this growing aging population with specific needs related to increased lifespan and limited financial resources, the use of emerging technologies, such as artificial intelligence (AI) and the Internet of Things (IoT), should be considered. As retirement ages rise and funds for retirement continue to decrease automated and sustainable solutions need to be sought. The ethical need to consider citizens not as customers but as decision-makers and to validate the ethical nature of medical decisions made for and by individuals should also be prioritized. This study provides recommendations for a smart city design and highlights the need for reflection on the ethics, modernization, and management of geriatric care. It suggests that technological devices can benefit health system reform by facilitating problem-solving. Overall, this new model integrates communal living and non-Western values with emerging technologies to address the growing need for geriatric care and the well-being of seniors.